NADP(H)-dependent biocatalysis without adding NADP(H) - Herold, RA; Reinbold, R; Schofield, CJ; Armstrong, FA (National Academy of Sciences, 2022)
Significance Within cells, enzymes and cofactors catalyzing multistep processes (cascades) are often confined together—either in enclosures (e.g., organelles) or via physical association (metabolons). Nanoconfinement, offering potential general advantages for catalysis, can also be achieved by loading enzymes and their exchangeable cofactors into a porous, electrically conducting inorganic material, thereby enabling catalysis to be channeled, energized, and investigated electrochemically. Such nanoconfinement enables a cascade comprising electroactive ferredoxin NADP+ reductase and isocitrate dehydrogenase to be active for days, catalyzing exhaustive oxidation of bulk isocitrate by recycling trapped NADP(H) carried in on isocitrate dehydrogenase. Nanoconfinement massively increases the efficiency of cofactor-dependent cascade catalysis and has conceptual relevance for prebiotic evolution where complex organic molecules might have formed in gaps and cracks of minerals. Abstract Isocitrate dehydrogenase 1 (IDH1) naturally copurifies and crystallizes in a resting state with a molecule of its exchangeable cofactor, NADP+/NADPH, bound in each monomer of the homodimer. We report electrochemical studies with IDH1 that exploit this property to reveal the massive advantage of nanoconfinement to increase the efficiency of multistep enzyme-catalyzed cascade reactions. When coloaded with ferredoxin NADP+ reductase in a nanoporous conducting indium tin oxide film, IDH1 carries out the complete electrochemical oxidation of 6 mM isocitrate (in 4mL) to 2-oxoglutarate (2OG), using only the NADP(H) that copurified with IDH1 and was carried into the electrode pores as cargo—the system remains active for days. The entrapped cofactor, now quantifiable by cyclic voltammetry, undergoes ~160,000 turnovers during the process. The results from a variety of electrocatalysis experiments imply that the local concentrations of the two nanoconfined enzymes lie around the millimolar range. The combination of crowding and entrapment results in a 102 to 103-fold increase in the efficiency of NADP(H) redox cycling. The ability of the method to drive cascade catalysis in either direction (oxidation or reduction) and remove and replace substrates was exploited to study redox-state dependent differences in cofactor binding between wild-type IDH1 and the cancer-linked R132H variant that catalyzes the “gain of function” reduction of 2OG to 2-hydroxyglutarate instead of isocitrate oxidation. The combined results demonstrate the power of nanoconfinement for facilitating multistep enzyme catalysis (in this case energized and verified electrochemically) and reveal insights into the dynamic role of nicotinamide cofactors as redox (hydride) carriers.